2015
DOI: 10.1111/ijfs.12780
|View full text |Cite
|
Sign up to set email alerts
|

Effects of light on growth, levels of anthocyanin, concentration of metabolites in Fagopyrum tataricum sprout cultures

Abstract: SumamyTartary buckwheat (Fagopyrum tataricum) sprouts are a popular healthy product around the world. The purpose of this study was to investigate the effects of light on growth, levels of anthocyanin, metabolite concentration in tartary buckwheat sprouts. To investigate the metabolites and accumulation of anthocyanin in tartary buckwheat sprouts, gas chromatography-mass spectrometry (GC-MS) and high performance liquid chromatography (HPLC) were conducted. The levels of Cyanidin 3-O-glucoside and Cyanidin 3-O-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 26 publications
2
11
0
Order By: Relevance
“…Anthocyanins, which are flavonoids, have been detected in Tartary buckwheat roots, leaves, stems, flowers, and shoots (Park et al, 2011;Peng et al, 2015). The antioxidant potency of anthocyanins is concentration-dependent (Gabrielska et al, 1999;Watanabe, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anthocyanins, which are flavonoids, have been detected in Tartary buckwheat roots, leaves, stems, flowers, and shoots (Park et al, 2011;Peng et al, 2015). The antioxidant potency of anthocyanins is concentration-dependent (Gabrielska et al, 1999;Watanabe, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have demonstrated that different anthocyanins accumulate during the various growth stages of buckwheat flowers (Suzuki et al, 2007). Additionally, the levels of anthocyanin present in tartary buckwheat sprouts was affected by exposure to specific light/dark cycles (Peng et al, 2015). However, to the best of our knowledge, no studies have focused on the changes in anthocyanin content and seed shape during different growth stages of tartary buckwheat seeds.…”
Section: Introductionmentioning
confidence: 99%
“…[16] Furthermore, chronic oxidative stress by free radicals can lead to diabetic complications, and thus antioxidants also have an important role for the prevention and treatment of T2D. [17,18] Numerous studies mainly focused on the germination of Tartary buckwheat sprout and accumulation of bioactive components, [19][20][21][22][23][24] antioxidant, [12,21,23] and α-glucosidase inhibitory activities. [12] However, there are few reports about the antioxidant activity, α-glucosidase inhibitory activity, phytochemical profiles, and quantitative analysis in the whole growth stages and various parts (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…These lamps increase photosynthetic photon flux levels, but they contribute little to plant growth. Plant development is strongly influenced by the light quality, which refers to the colour or wavelength reaching a plant's surface (Johkan et al ., ; Peng et al ., ). While it is widely understood that light intensity can positively affect photochemical accumulation (Li & Kubota, ), the effects of light quality are more complex, and mixed results are often reported.…”
Section: Introductionmentioning
confidence: 99%